Pengaruh Word Of Mouth Dan Customer Experience Terhadap Kepuasan Mahasiswa Menggunakan Bsb Syariah Pembayaran UKT Mahasiswa UIN Raden Fatah Palembang - Ayu Lestari; Lemiyana; M. Junestrada Diem (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2024)
Word of mouth is communication by word of mouth regarding the quality of a product. Customer experience is a series or strategy and implementation carried out by a company to manage relationships with customers regarding the use of the company's products or services. This research aims to analyze the influence of word of mouth and customer experience on student satisfaction in using BSB Syariah services for paying Single Tuition Fees (UKT) at UIN Raden Fatah Palembang This type of research uses quantitative research with Likert scale questionnaire data collection techniques. The object of this research is undergraduate students in Sharia Banking class 2020 and 2021, Faculty of Islamic Economics and Business, UIN Raden Fatah Palembang. The number of respondents was 83 with a questionnaire of 32 statements. The research results show that word of mouth has a positive and significant effect on student satisfaction, with a t-count value of 4.285 which is greater than t-table 1.644 and a significance value of 0.000 which is smaller than 0.05. Furthermore, customer experience is also proven to have a positive and significant influence on student satisfaction, with a t value of 6.399 which is greater than t table 1.644 and a significance value of 0.000 which is smaller than 0.05. Together, word of mouth and customer experience have a significant effect on student satisfaction, with an Fcount value of 114.533 which is greater than Ftable 3.11 and a significance value of 0.000 which is smaller than 0.05. Thus, the combination of word of mouth and customer experience plays an important role in increasing student satisfaction with BSB Syariah services.